A magnesium ion doped strontium zirconate infrared / radar compatible stealth material and a preparation method and application thereof
Patent Information
- Application Number
- CN202610981526.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-02
- Publication Date
- 2026-10-27
AI Technical Summary
CN117534460A未涉及如介电损耗、界面极化、反射损耗(RL)、有效吸收带宽等与雷达隐身相关的性能
与现有SrZrO3基红外隐身材料相比,本发明通过Mg2+对锆位的部分取代,在保持钙钛矿主相结构稳定的同时,引入可控浓度的氧空位缺陷。该缺陷结构一方面通过激活红外活性声子振动模式和细化晶粒,实现了红外发射率在0.595~0.735范围内的宽幅可调;另一方面,氧空位在交变电磁场中产生偶极极化损耗,结合晶界引起的界面极化损耗,显著增强了材料对雷达波的介电吸收能力。
Smart Images

Figure CN122977435A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of stealth materials technology, specifically relating to a magnesium ion-doped strontium zirconate infrared / radar compatible stealth material, its preparation method, and its application. Background Technology
[0002] With the rapid development of infrared detection technology, the demand for infrared stealth in high-temperature components of military aircraft (such as engine exhaust nozzles and wing leading edges) is becoming increasingly urgent. Existing infrared stealth materials mainly include three categories: metal-based, polymer-based, and inorganic oxide-based. Among them, metal-based materials are easily oxidized at high temperatures, and their infrared emissivity increases sharply with increasing temperature, while polymer-based materials have poor thermal stability and cannot be used for extended periods above 300°C.
[0003] Inorganic oxide-based materials, represented by perovskite-structured strontium zirconate (SrZrO3), are among the most promising matrix materials for high-temperature infrared stealth due to their high melting point, good high-temperature phase stability, and tunable optical properties. However, existing SrZrO3-based materials exhibit relatively high infrared emissivity in the 3–5 μm military detection band and lack radar wave absorption capabilities, making it difficult to achieve multi-band infrared and radar-compatible stealth.
[0004] In the prior art, such as CN117534460A, CN117550890A, and CN120230986A, a series of Sr(Zr) materials are disclosed. 1-y X y )O z Material coatings, wherein X is Mg, Ca, Mn, Fe, Co, Ni, Cu, or Zn; y is 0.05~0.5, and z is 2.5~2.9375. However, these methods produce high infrared radiation coatings, which cannot provide effective infrared and radar multi-band compatible stealth performance. A search revealed that CN117534460A discloses a class of Sr(Zr) coatings. 1-y X y )O z Perovskite materials, where X includes elements such as Mg, Ca, Mn, Fe, Co, Ni, Cu, and Zn. The technical objective of this document is to improve the infrared emissivity of the material in the 3–5 μm and 1–22 μm wavelength bands to meet the requirements of energy saving in high-temperature furnaces, heat dissipation of devices, and thermal protection applications. Its core focus is on improving infrared radiation performance. CN117534460A does not address performance related to radar stealth, such as dielectric loss, interface polarization, reflection loss (RL), and effective absorption bandwidth.
[0005] In the prior art, such as CN110746186A, an Al 3+ Doped low-infrared, low-thermal-conductivity semiconductor ceramic material with the molecular formula SrZr 1-x Alx O3, where x is Al 3+ The percentage of Zr atoms doped. However, the technical goal of CN110746186A is to obtain ceramic materials with low infrared emissivity and low thermal conductivity. Its performance evaluation indicators mainly include infrared emissivity and thermal conductivity in the 3-5 μm band. However, this document does not address performance parameters related to electromagnetic wave absorption, such as the material's dielectric constant, dielectric loss, reflection loss, and effective absorption bandwidth. Therefore, this document can only solve the infrared stealth problem, but cannot achieve the electromagnetic wave absorption function required for infrared and radar wave compatible stealth. It is evident that current technologies have not yet effectively realized the application of perovskite structure materials in infrared and radar wave stealth materials. Summary of the Invention
[0006] The purpose of this invention is to address at least one of the aforementioned problems by providing a magnesium ion-doped strontium zirconate infrared / radar compatible stealth material, its preparation method, and its applications, thereby overcoming the difficulty in achieving multi-band infrared and radar compatibility stealth using existing SrZrO3-based materials. This solution utilizes magnesium ion-doped strontium zirconate to achieve a wide-range adjustable infrared emissivity within the range of 0.595 to 0.735 and enhances the material's dielectric absorption capability for radar waves.
[0007] The objective of this invention is achieved through the following technical solution: The first aspect of this invention discloses a method for preparing magnesium ion-doped strontium zirconate infrared / radar compatible stealth material, comprising the following steps: S1. Dissolve the strontium source, zirconium source and magnesium source in deionized water to prepare a mixed metal solution; S2. Add a complexing agent to the mixed metal solution in step S1, then adjust the pH to acidic, and heat in a water bath to form a sol. S3. The sol formed in step S2 is dried, ground, and calcined at high temperature in sequence to obtain the nanoparticles, which are the material described above.
[0008] Preferably, step S1 includes: The molar ratio of strontium source, zirconium source and magnesium source is 1:1-x:x; where x is 0.03 to 0.21. The strontium source is strontium nitrate, the zirconium source is zirconium nitrate pentahydrate, and the magnesium source is magnesium nitrate hexahydrate.
[0009] Preferably, step S2 includes: The complexing agent is citric acid; The molar ratio of the complexing agent to the metal ions in the mixed metal solution is 1.5:1 to 2.5:1.
[0010] Preferably, step S2 includes: Adjusting the pH to acidic means adjusting the pH to 2-4.
[0011] Preferably, step S2 includes: The conditions for water bath heating are as follows: The temperature is 40℃~60℃; The time is 4 to 8 hours.
[0012] Preferably, step S3 includes: The drying conditions are as follows: The temperature is 100℃~150℃; The time is 12~48 hours.
[0013] Preferably, step S3 includes: The conditions for the high-temperature calcination are as follows: The temperature is 1000℃~1200℃; The time is 4 to 10 hours.
[0014] The second aspect of this invention discloses a magnesium ion-doped strontium zirconate infrared / radar compatible stealth material, which is obtained by the preparation method described in any of the preceding claims; The chemical formula of the material is SrZr 1-x Mg x O3; Where x ranges from 0.03 to 0.21.
[0015] The third aspect of this invention discloses the application of magnesium ion-doped strontium zirconate infrared / radar compatible stealth material as described above in infrared stealth materials.
[0016] Preferably, the infrared emissivity of the infrared stealth material is 0.595~0.735.
[0017] The working principle of this invention is as follows: Mg 2+ After entering the SrZrO3 lattice, it preferentially replaces Zr. 4+ Location. Due to Mg 2+ With Zr 4+ There are valence state differences between the Mg and Mg, and to maintain charge balance, a certain concentration of oxygen vacancy defects are formed within the crystal lattice. As defect dipole centers, these oxygen vacancies can undergo defect dipole polarization relaxation and consume electromagnetic energy under the influence of an alternating electromagnetic field; simultaneously, Mg... 2+ Doping-induced lattice distortion, defect enrichment regions, and changes in grain boundary structure can further enhance the interfacial polarization effect, thereby improving the dielectric loss capability of the material. Furthermore, the modulation of oxygen vacancy concentration can alter the lattice vibrational state and local electronic structure, achieving modulation of infrared characteristics in the 3–5 μm band. Therefore, this invention utilizes Mg… 2+By inducing oxygen vacancy defects through doping, the synergistic optimization of infrared feature modulation and electromagnetic wave attenuation capability is achieved, resulting in a compatible stealth material that combines infrared stealth and radar stealth capabilities.
[0018] Compared with the prior art, the present invention has the following beneficial effects: Compared with existing SrZrO3-based infrared stealth materials, this invention utilizes Mg 2+ Partial substitution at zirconium sites introduces oxygen vacancy defects with controllable concentrations while maintaining the stability of the perovskite main phase structure. This defect structure, on the one hand, activates infrared active phonon vibration modes and refines grains, achieving a wide range of adjustable infrared emissivity from 0.595 to 0.735; on the other hand, oxygen vacancies generate dipole polarization losses in alternating electromagnetic fields, which, combined with interfacial polarization losses caused by grain boundaries, significantly enhance the material's dielectric absorption capability for radar waves.
[0019] The material prepared by this method exhibits infrared and radar wave absorption capabilities in the 3-5 μm band, achieving infrared and radar band compatible stealth. The material demonstrates good high-temperature stability and structural controllability. The SrZrO3 matrix used is a high-melting-point perovskite oxide ceramic with a melting point of approximately 2700℃; Mg... 2+ Even after doping, it maintains a stable crystal phase structure, thus the material possesses excellent high-temperature service potential and structural stability, making it suitable for multi-spectral stealth protection applications such as high-temperature components in aero-engines. This invention utilizes Mg... 2+ Doping induces oxygen vacancy defects and lattice distortion, thereby modulating the infrared characteristics and electromagnetic response behavior of the material while maintaining the stability of the SrZrO3 perovskite structure.
[0020] Compared to existing materials, this invention targets stealth applications compatible with both infrared and radar waves. The material not only enables infrared signature modulation but also possesses excellent electromagnetic wave attenuation and impedance matching characteristics. Specifically, this invention utilizes Mg... 2+ Replace Zr 4+ Introducing controllable oxygen vacancy defects can enhance dielectric loss and interface polarization effects while achieving infrared feature modulation, thereby obtaining radar wave absorption capability. The technical problems solved and the implementation mechanisms of the two methods are fundamentally different. Attached Figure Description
[0021] Figure 1 SrZr prepared in Example 1 of this invention 1-x Mg x X-ray diffraction patterns of O3 powder and SrZrO3 powder prepared in Comparative Example 1.
[0022] Figure 2 The reflection loss curves of the SZMO-1 sample prepared in Example 1 of this invention under different matching thicknesses are shown. Detailed Implementation
[0023] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments.
[0024] Unless otherwise specified in the following description, the reagents used are conventional commercial products, the methods used are well-known in the art, and any other matters not covered herein may be handled using existing technologies.
[0025] A magnesium ion-doped strontium zirconate infrared / radar compatible stealth material and its preparation method, comprising the following steps: (1) Strontium source, zirconium source and magnesium source are dissolved in deionized water in stoichiometric ratio, citric acid is added as a complexing agent, the pH is adjusted to acidic, and a sol is formed by heating in a water bath. (2) After drying, grinding and high-temperature calcination, the chemical formula SrZr is obtained. 1-x Mg x O3 nanoparticles, where x is 0.03 to 0.21.
[0026] The above step (1) uses strontium nitrate as the strontium source, zirconium pentahydrate as the zirconium source, and magnesium hexahydrate as the magnesium source.
[0027] In step (1) above, the molar ratio of citric acid to metal ions is 1.5:1 to 2.5:1, more preferably 2:1.
[0028] Step (1) above: Adjust pH to 2-4.
[0029] The above step (1): the water bath heating temperature is 40℃~60℃, and the time is 4~8h.
[0030] Step (2) above: The drying temperature is 100℃~150℃, and the time is 12~48h.
[0031] The above step (2): the high temperature of calcination is 1000℃~1200℃, and the time is 4~10h.
[0032] Example 1 Strontium nitrate, zirconium nitrate pentahydrate, and magnesium nitrate hexahydrate were weighed according to a stoichiometric ratio of Sr:Zr:Mg = 1:0.97:0.03, with a total metal ion molar number of 0.05 mol. The above nitrates were dissolved in 50 mL of deionized water and stirred at room temperature until completely dissolved. Citric acid solid (approximately 14.4 g) was weighed according to a citric acid to metal ion molar ratio of 1.5:1 and slowly added to the above solution, with stirring continued for 15 min. The pH of the solution was adjusted to 3 using 25%–28% ammonia solution. The solution was placed in a 40℃ constant temperature water bath and stirred at 420 r / min for 4 h to obtain a sol. The sol was allowed to stand at room temperature for 2 h, then transferred to a forced-air drying oven and dried at 100℃ for 48 h to obtain a dry gel. The dry gel was ground and placed in a muffle furnace. The temperature was increased to 500℃ at 3℃ / min, then increased to 1000℃ at 5℃ / min, and held for 10 hours. The mixture was then cooled in the furnace to obtain white nanoparticles, which were designated as SZMO-1.
[0033] The material was tested and found to have an infrared emissivity of 0.601 in the 3–5 μm band; with a thickness of 8.0 mm, the reflection loss across the entire 2–18 GHz band was ≤-10 dB. The infrared emissivity was measured using a Fourier transform infrared spectrometer (FTIR), and the average infrared emissivity was calculated by comparing it with a standard blackbody radiation source. Radar absorption performance was tested using a vector network analyzer. The sample was mixed with paraffin wax in a specific ratio and pressed into a standard toroidal specimen. Its complex permittivity and complex permeability were measured in the 2–18 GHz band, and the reflection loss (RL) was calculated based on transmission line theory.
[0034] Example 2 The operating steps in this embodiment are the same as in Example 1, except that: the raw materials are weighed according to the molar ratio of Sr:Zr:Mg = 1:0.91:0.09; the molar ratio of citric acid to metal ions is 2:1 (approximately 19.2 g of solid citric acid); the pH is adjusted to 3; the water bath temperature is 50℃ for 6 hours; the drying temperature is 120℃ for 24 hours; and the calcination temperature is 1100℃ for 6 hours. The resulting powder is designated as SZMO-2.
[0035] Tests showed that the material has an infrared emissivity of 0.672 in the 3-5μm band; and a reflection loss of ≤-10dB in the 15.5-18GHz band at a thickness of 2.0mm.
[0036] Example 3 The operating steps in this embodiment are the same as in Embodiment 1, except that: the raw materials are weighed according to the molar ratio of Sr:Zr:Mg = 1:0.85:0.15; the molar ratio of citric acid to metal ions is 2.5:1 (approximately 24.0 g of solid citric acid); the pH is adjusted to 4; the water bath temperature is 55℃ for 7 hours; the drying temperature is 130℃ for 36 hours; and the calcination temperature is 1150℃ for 8 hours. The resulting powder is designated as SZMO-3.
[0037] Tests showed that the material has an infrared emissivity of 0.735 in the 3-5 μm band; with a thickness of 2.0 mm, the reflection loss in the full Ku band from 12 to 18 GHz is ≤-10 dB, and the minimum reflection loss reaches -18.7 dB.
[0038] Example 4 The operating steps in this embodiment are the same as in Embodiment 1, except that: the raw materials are weighed according to the molar ratio of Sr:Zr:Mg = 1:0.79:0.21; the molar ratio of citric acid to metal ions is 2.5:1 (same as in Embodiment 3); the pH is adjusted to 3.5; the water bath temperature is 60℃ for 8 hours; the drying temperature is 150℃ for 12 hours; and the calcination temperature is 1200℃ for 4 hours. The resulting powder is designated as SZMO-4.
[0039] Tests showed that the material has an infrared emissivity of 0.731 in the 3-5 μm band and a reflection loss of ≤-10 dB across the 2-18 GHz band with a thickness of 8.0 mm.
[0040] Comparative Example 1 The operating steps are the same as in Example 2 (i.e., using intermediate parameters), except that magnesium nitrate hexahydrate is not added, i.e., Sr:Zr = 1:1. Pure phase SrZrO3 powder is obtained, denoted as SZO.
[0041] Tests showed that the material has an infrared emissivity of 0.595 in the 3-5μm band, but no effective microwave absorption performance (the reflection loss is higher than -5dB in the 2-18GHz band).
[0042] Figure 1 The X-ray diffraction patterns of the SrZrO3 crystal samples prepared in Example 1 and Comparative Example 1 are shown in the figures. As can be seen from the figures, both the SZMO-1 sample obtained in Example 1 and the SrZrO3 sample in the comparative example exhibit typical perovskite structure diffraction peaks. The positions of each diffraction peak are consistent with the PDF card of standard SrZrO3. No obvious impurity phase peaks were found, indicating that Mg... 2+ The Mg successfully entered the SrZrO3 lattice and maintained the stability of the main crystal phase structure. Compared with pure SrZrO3, the diffraction peaks of the doped sample showed slight shifts and changes in peak shape, indicating that Mg... 2+Doping induces lattice distortion and defect structure formation, consistent with the introduction of oxygen vacancy defects. Compared to pure SrZrO3, the doped sample exhibits a slight shift and broadening of diffraction peaks, indicating that Mg... 2+ Upon entering the crystal lattice, it causes local lattice distortion and an increase in microstrain. This is due to Mg... 2+ With Zr 4+ There are differences in ionic radius and valence state between them, and oxygen vacancy defects will form in order to maintain charge balance. This result is consistent with the Mg proposed in this invention. 2+ Replace Zr 4+ This is consistent with the mechanism that induces oxygen vacancies. The aforementioned lattice distortions and oxygen vacancy defects not only facilitate the modulation of infrared features, but also provide a structural basis for subsequent defect polarization and interface polarization, thereby enhancing the material's ability to attenuate electromagnetic waves.
[0043] Comparative Example 2 The operating steps for this comparative example are the same as in Example 1, except that the raw materials are weighed according to the molar ratio of Sr:Zr:Mg = 1:0.99:0.01, i.e., Mg 2+ The doping amount is below the range specified in this invention. The remaining molar ratios of citric acid to metal ions, pH, water bath temperature, drying conditions, and calcination conditions are the same as in Example 1. The resulting powder is designated SZMO-D1.
[0044] Testing revealed that the material's infrared emissivity in the 3–5 μm band is close to that of pure-phase SrZrO3, but its radar absorption performance is not significantly improved, and it does not form a continuous effective absorption band in the 2–18 GHz range. This indicates that when the Mg doping level is too low, the oxygen vacancy defect concentration in the material is insufficient, making it difficult to effectively enhance dipole polarization loss and interfacial polarization loss, thus failing to achieve ideal infrared / radar compatible stealth performance.
[0045] Comparative Example 3 The operating steps for this comparative example are the same as in Example 1, except that the raw materials are weighed according to the molar ratio of Sr:Zr:Mg = 1:0.75:0.25, i.e., Mg 2+ The doping amount exceeded the range specified in this invention. The remaining molar ratios of citric acid to metal ions, pH, water bath temperature, drying conditions, and calcination conditions were the same as in Example 1. The resulting powder was designated SZMO-D2.
[0046] Testing revealed that while the material possesses some radar wave absorption capability, its infrared emissivity further increases, and its phase stability decreases, making it prone to excessive lattice distortion or the formation of local impurity phases. This indicates that when Mg... 2+ When the doping level is too high, excess Mg 2+ Entering the SrZrO3 lattice disrupts the stability of the perovskite main phase structure and leads to an unfavorable increase in infrared emissivity, making it unsuitable for use in infrared / radar compatible stealth materials.
[0047] As can be seen from Examples 1-4 and the comparative examples, when Mg 2+ When the doping concentration is below 0.03%, the oxygen vacancy defect concentration is insufficient, making it difficult to effectively improve radar wave absorption performance; when Mg 2+ When the doping concentration is higher than 0.21, the infrared emissivity of the material increases and the stability of the main phase structure decreases. Therefore, this invention uses Mg 2+ By limiting the doping amount to 0.03~0.21 and the pH to 2~4, it is possible to achieve infrared emissivity regulation and radar wave absorption performance improvement while maintaining the stability of the SrZrO3 perovskite structure.
[0048] In summary, this solution proposes a magnesium ion-doped strontium zirconate infrared / radar compatible stealth material and its preparation method. The preparation process is simple, the synthesis temperature is low, the product purity is high, and it provides effective infrared / radar dual stealth within a certain range.
[0049] The above description of the embodiments is provided to enable those skilled in the art to understand and use the invention. It will be apparent to those skilled in the art that various modifications can be made to these embodiments, and the general principles described herein can be applied to other embodiments without inventive effort. Therefore, the present invention is not limited to the above embodiments, and any improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the invention should be within the protection scope of the present invention.
Claims
1. A method for preparing a magnesium ion-doped strontium zirconate infrared / radar compatible stealth material, characterized in that, Includes the following steps: S1. Dissolve the strontium source, zirconium source and magnesium source in deionized water to prepare a mixed metal solution; S2. Add a complexing agent to the mixed metal solution in step S1, then adjust the pH to acidic, and heat in a water bath to form a sol. S3. The sol formed in step S2 is dried, ground, and calcined at high temperature in sequence to obtain the nanoparticles, which are the material described above.
2. The preparation method of a magnesium ion-doped strontium zirconate infrared / radar compatible stealth material according to claim 1, characterized in that, Step S1 includes: The molar ratio of strontium source, zirconium source and magnesium source is 1:1-x:x; where x is 0.03 to 0.
21. The strontium source is strontium nitrate, the zirconium source is zirconium nitrate pentahydrate, and the magnesium source is magnesium nitrate hexahydrate.
3. The preparation method of a magnesium ion-doped strontium zirconate infrared / radar compatible stealth material according to claim 1, characterized in that, Step S2 includes: The complexing agent is citric acid; The molar ratio of the complexing agent to the metal ions in the mixed metal solution is 1.5:1 to 2.5:
1.
4. The preparation method of a magnesium ion-doped strontium zirconate infrared / radar compatible stealth material according to claim 1, characterized in that, Step S2 includes: Adjusting the pH to acidic means adjusting the pH to 2-4.
5. The preparation method of a magnesium ion-doped strontium zirconate infrared / radar compatible stealth material according to claim 1, characterized in that, Step S2 includes: The conditions for water bath heating are as follows: The temperature is 40℃~60℃; The time is 4 to 8 hours.
6. The preparation method of a magnesium ion-doped strontium zirconate infrared / radar compatible stealth material according to claim 1, characterized in that, Step S3 includes: The drying conditions are as follows: The temperature is 100℃~150℃; The time is 12~48 hours.
7. The method for preparing a magnesium ion-doped strontium zirconate infrared / radar compatible stealth material according to claim 1, characterized in that, Step S3 includes: The conditions for the high-temperature calcination are as follows: The temperature is 1000℃~1200℃; The time is 4 to 10 hours.
8. A magnesium ion-doped strontium zirconate infrared / radar compatible stealth material, characterized in that, Obtained by the preparation method described in any one of claims 1 to 7; The chemical formula of the material is SrZr 1-x Mg x O3; Where x ranges from 0.03 to 0.
21.
9. The application of the magnesium ion-doped strontium zirconate infrared / radar compatible stealth material as described in claim 8 in infrared stealth materials.
10. The application according to claim 9, characterized in that, The infrared emissivity of the infrared stealth material is 0.595~0.735.
Citation Information
Patent Citations
Al<3+> doped low-infrared and low-thermal-conductivity semiconductor ceramic material and preparation method thereof
CN110746186A
High-infrared-emissivity perovskite type ceramic material and preparation method and application thereof
CN117534460A
Preparation method and application of high-temperature high-infrared-emissivity ceramic material
CN117550890A
Coating with high temperature, high infrared emissivity and low thermal conductivity as well as preparation method and application of coating
CN120230986A